2004
DOI: 10.1159/000074957
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Neonatal Pig Heart Subjected to Oxygen Insufficiency

Abstract: Isolated, paced, isovolumically beating, neonatal pig (n = 32) hearts underwent retrograde aortic perfusion with a solution containing insulin (100 µU/ml), glucose (5.5 mM), and palmitate (0.55 mM). Glycolysis, lactate release, glucose oxidation, palmitate oxidation, and oxygen consumption were assessed. The hearts were perfused during three periods: (1) baseline, pO2 ≈ 500 mm Hg, heart rate 150 bpm; (2) hypoxia, pO2 ≈ 60–80 mm Hg, heart rate 150 bpm, or tachycardia, pO2 ≈ 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This was primarily due to increased HR, not augmented LVDP. The findings agree with previous experiments (Penn et al 1999;Ascuitto et al 1999, Uy et al 2004, which demonstrated an adverse effect of accelerated-paced HR on left ventricular pressure development and LVEDP in the isolated isovolumically beating heart. The mechanisms of these effects are not completely clear.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was primarily due to increased HR, not augmented LVDP. The findings agree with previous experiments (Penn et al 1999;Ascuitto et al 1999, Uy et al 2004, which demonstrated an adverse effect of accelerated-paced HR on left ventricular pressure development and LVEDP in the isolated isovolumically beating heart. The mechanisms of these effects are not completely clear.…”
Section: Discussionsupporting
confidence: 93%
“…However, other investigators (Goodwin et al 1998;Ochiai et al 2001) have contested this view. Uy et al (2004) demonstrated that, although pacing the isolated neonatal pig heart at 300 bpm (a much higher rate than in our study) created an oxygen supply/demand ratio similar to that of hypoxia, oxygen extraction was measured at approximately 50%, indicating adequate oxygen availability. Therefore, it seems unlikely that the inability of the hearts to maintain LVDP in our model was a direct effect of the mismatch between oxygen supply and demand.…”
Section: Figmentioning
confidence: 49%